Energy Storage Innovations in the Context of Electric Vehicles and Smart Grid Integration: A Review - Ehtesham Ali; Rahool Rai; Muhammad Aleem; Rafiq Asghar; Rittick Maity (International Journal of Economic and Environment Geology)
The integration of electric vehicles (EVs) with the smart grid presents a transformative solution for achieving energy efficiency and environmental sustainability. Thispaper explores advanced energy storage devices and management systems that enhance the operational flexibility and stability of EVs within a smart grid context. By enabling bidirectional power flows in Vehicle-to-Grid (V2G) and Grid-to-Vehicle (G2V) modes, EVs not only function as transportation but also as distributed energy resources that support grid demand management, especially during peak and off-peak hours. This paper shows that lithium-ion (Li-ion) and sodium-nickel chloride (Na-NiCl) batteries exhibit superior energy density and efficiency, making them ideal for EV applications where high energy storage and extended cycle life are crucial. The study reveals that Li-ion polymer batteries, with their high specific energy, are widely used in portable devices and EVs, while Na-NiCl batteries, with the highest efficiency (92.5%), are particularly suited for long-term energy storage. The study provides new insights into managing EV energy storage within a smart grid by enabling stable, bidirectional energy flows. Additionally, smart grid integration through wide-area EV networks can stabilize grid operations by balancing supply-demand dynamics, reducing CO₂ emissions, and enhancing energy resilience. The implications for EV infrastructure, policy, and future technological development highlight EVs' role in advancing sustainable, high-efficiency energy systems